Modelling the influence of strain localisation and viscosity on the behaviour of underground drifts drilled in claystone. (May 2017) - Pardoen, B.; Collin, F.
Abstract: A benchmark is conducted to characterise the Callovo-Oxfordian claystone behaviour for nuclear waste repository. The objective is to model gallery drilling and Excavation Damaged Zone (EDZ) around galleries. The proposed model is a cross-anisotropic elasto-viscoplastic model whose parameters are calibrated from laboratory tests. Gallery drilling is modelled numerically and shear fractures are reproduced with shear bands. The modelling highlights the contributions of shear banding, viscosity, and anisotropy for the EDZ behaviour. The EDZ and the gallery convergence can be correctly represented only if fractures are reproduced. Modelling shear banding is crucial and leads to a better description of the EDZ.